Comparison of the efficacy of Intra articular Hyaluronic acid and Triamcinolone acetonide in the treatment of Osteoarthritis of Knee - Mariappan, Selvamari; Kumar, Satish; Varshney, Anurag (Journal of Neonatal Surgery, 2025)
Introduction: The aim of the study is to compare the efficacy of Intra articular Hyaluronic acid and Triamcinolone acetonide in the treatment of Osteoarthritis of Knee. Materials and methods: A Randomised Control Study was done in Dhanalakshmi Srinivasan medical college Hospital between May 2024 and November 2024. Ethical clearance was not obtained. A total number of 40 patients were included in the study. 40 patients were recruited in two groups namely Group A who received Hyaluronic Acid (HA), Group B received Triamcinolone Acetonide (TA). Assessment was done using VAS scale, after one week, one month & 6 months of getting Intra articular Injection. Using SPSS Software Mean & Standard Deviation was calculated. Results: The mean age of the patients was 67.4± 8 years (Range 57-82). At first week mean VAS score was 3.25±1.372 for HA and 2.55±1.276 for TA(p<0.05). After one month the VAS score was 3.05±1.538 for HA and 3.1±1.334 for TA (p>0.05). After one month of injection the VAS score was 3.4±1.429 for HA and 3.85±1.182 for TA (p>0.05). Conclusion: After one week of Intraarticular injection, TA group had less pain compared to HA group. Both the groups have significant decrease of pain clinically, but there was no significant decrease pain between the groups statistically after one month and 6 months.